Polypropylene-based resin foamed particle

JP2025022511APending Publication Date: 2025-02-14JSP CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023127165
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0009】 型内成形時におけるスチームの圧力を著しく低減できるとともに、養生時間を短縮することができ、更に、養生時間を短縮しても、目的の形状を有し、外観に優れた発泡粒子成形体を得ることができる発泡粒子を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022511000001
    Figure 2025022511000001
  • Figure 2025022511000002
    Figure 2025022511000002
Patent Text Reader

Abstract

To provide a foamed particle capable of remarkably reducing a pressure of steam when molding in a mold, and shortening a curing time, and further capable of obtaining a foamed particle molding excellent in appearance, and having an aimed shape even if the curing time is shortened.SOLUTION: A polypropylene-based foamed particle has: a foamed core layer composed of a polypropylene-based resin; and a coating layer for coating the foamed core layer, where the coating layer is composed of a linear low-density polyethylene, a mass ratio of the coating layer with respect to the foamed core layer is 0.005 to 0.05, and the polypropylene-based resin composed of the foamed core layer is one or more kinds of copolymers ii selected from (i) an ethylene-butene-propylene copolymer having a total amount of an ethylene constituent and a butene constituent of 3.5 mass% or more, or (ii) an ethylene-propylene copolymer having a total amount of an ethylene constituent and a butene constituent of 4.0 mass% or more, and a butane-propylene copolymer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an expanded polypropylene resin particle. [Background technology]

[0002] Polypropylene resin expanded bead moldings are used in various applications because they are lightweight and have excellent cushioning properties, rigidity, etc. Examples of methods for producing polypropylene resin expanded bead moldings include an in-mold molding method in which polypropylene resin expanded beads are filled into a mold and heated with steam to secondary expand the expanded beads and melt their surfaces to fuse them together, forming them into a desired shape, and then cooling them in the mold with water, air, or the like, followed by releasing them from the mold.

[0003] If the foamed bead molding is stored at room temperature after in-mold molding, the steam that flows into the bubbles of the foamed bead molding during in-mold molding and remains therein condenses in the bubbles, creating negative pressure in the bubbles, causing the foamed bead molding to shrink in volume and to become significantly deformed. Therefore, after releasing the foamed bead molding, a curing step is required in which the foamed bead molding is left to stand for a predetermined time in a high-temperature atmosphere adjusted to a temperature of about 60°C to 80°C to restore its shape. The curing step is a long process that requires, for example, about 12 hours.

[0004] Therefore, methods for shortening the curing time have been studied to improve productivity.For example, Patent Document 1 discloses an expanded bead molding that does not require special equipment or processes, is easy to dry, and reduces dimensional shrinkage to make a high-temperature curing process unnecessary, and is obtained by filling a mold with expanded beads consisting of an expanded core layer made of a crystalline thermoplastic resin and a non-expanded coating layer, introducing steam or hot air into the mold to heat and fuse the expanded beads, and in which the portions where the coating layers are in contact with each other form fused portions and gaps are formed between the expanded beads. Furthermore, Patent Document 2 discloses expanded polypropylene resin particles that have as their base resin a propylene random copolymer or random block copolymer having a melt flow index, Z-average molecular weight, melting point, and endothermic energy of an endothermic peak appearing on the high-temperature side of a DSC curve within a specific range, as expanded particles that can shorten the curing time and improve secondary foaming properties, fusion properties, and cracking resistance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2003-039565 A [Patent Document 2] JP 2000-129028 A Summary of the Invention [Problem to be solved by the invention]

[0006] The technique described in Patent Document 1 can omit the curing step, but many voids are formed between the expanded beads in the molded body, so that the appearance of the resulting expanded bead molded body is extremely poor and it cannot be used for some applications. The technique described in Patent Document 2 can shorten the curing step, but there is room for improvement in its effectiveness. In addition, the technique described in Patent Document 2 requires a high steam pressure for molding, which places a heavy load on the equipment. Therefore, there is a need for a method to solve the above problems, in particular a method to reduce the steam pressure and shorten the curing step.

[0007] Therefore, an object of the present invention is to provide expanded beads that can significantly reduce the steam pressure during in-mold molding, can shorten the curing time, and can provide an expanded bead molding having a desired shape and excellent appearance even with the shortened curing time. [Means for solving the problem]

[0008] The present inventors have found that the above problems can be solved by adopting the configuration described below, and have completed the present invention. That is, the present invention is as follows. <1> A polypropylene-based resin expanded particle having an expanded core layer composed of a polypropylene-based resin and a coating layer coating the expanded core layer, the coating layer being composed of a linear low-density polyethylene, the mass ratio of the coating layer to the expanded core layer being 0.005 or more and 0.05 or less, and the polypropylene-based resin constituting the expanded core layer satisfying the following (i) or (ii): (i) the polypropylene-based resin constituting the foamed core layer is an ethylene-butene-propylene copolymer i, and the total amount Ccmt of the ethylene component and the butene component in the copolymer i (i) is 3.5 mass% or more (ii) the polypropylene-based resin constituting the foamed core layer is one or more copolymers ii selected from an ethylene-propylene copolymer and a butene-propylene copolymer, and the total amount Ccmt of the ethylene component and the butene component in the copolymer ii (ii) is 4.0 mass% or more <2> the linear low-density polyethylene constituting the coating layer is a resin polymerized using a Ziegler-Natta polymerization catalyst; <1> 2. The expanded polypropylene resin particles according to claim 1 . <3> The flexural modulus of the polypropylene-based resin constituting the foamed core layer is 400 MPa or more and less than 800 MPa. <1> or <2> 2. The expanded polypropylene resin particles according to claim 1 . <4> The average thickness (Tt) of the coating layer is 0.1 μm or more and 5 μm or less. <1> ~ <3> 10. The expanded polypropylene resin particles according to claim 9 . <5> The polypropylene-based resin constituting the foamed core layer is an ethylene-butene-propylene copolymer i. <1> ~ <4> 10. The expanded polypropylene resin particles according to claim 9 . <6> The polypropylene resin constituting the foamed core layer is a resin polymerized using a Ziegler-Natta polymerization catalyst. <1> ~ <5> 10. The expanded polypropylene resin particles according to claim 9 . <7> The flexural modulus of the linear low-density polyethylene constituting the coating layer is 120 MPa or more and 600 MPa or less. <1> ~ <6> 10. The expanded polypropylene resin particles according to claim 9 . <8> The bulk ratio of the expanded beads is 5 times or more and 45 times or less. <1> ~ <7> 10. The expanded polypropylene resin particles according to claim 9 . Effect of the Invention

[0009] It is possible to provide expanded beads that can significantly reduce the steam pressure during molding in a mold and shorten the curing time, and further, can provide an expanded bead molding having a desired shape and excellent appearance even with the shortened curing time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The expanded polypropylene-based resin particles of the present invention (hereinafter also simply referred to as expanded polypropylene-based resin particles or expanded particles) are expanded polypropylene-based resin particles having an expanded core layer composed of a polypropylene-based resin and a coating layer coating the expanded core layer, wherein the coating layer is composed of linear low-density polyethylene, the mass ratio of the coating layer to the expanded core layer is 0.005 or more and 0.05 or less, and the polypropylene-based resin constituting the expanded core layer satisfies the following (i) or the following (ii). (i) the polypropylene-based resin constituting the foamed core layer is an ethylene-butene-propylene copolymer i, and the total amount Ccmt of the ethylene component and the butene component in the copolymer i (i) is 3.5 mass% or more (ii) the polypropylene-based resin constituting the foamed core layer is one or more copolymers ii selected from an ethylene-propylene copolymer and a butene-propylene copolymer, and the total amount Ccmt of the ethylene component and the butene component in the copolymer ii (ii) is 4.0 mass% or more

[0011] The expanded polypropylene resin beads of the present invention, having the above-mentioned configuration, can significantly reduce the steam pressure during in-mold molding and can shorten the curing time. Furthermore, even if the curing time is shortened, an expanded bead molding having a desired shape and excellent appearance can be obtained. In this specification, "shortening the time required for the curing step (curing time)" refers to, for example, shortening the time required for the curing step, which usually requires leaving the molded body after release in a high-temperature environment of about 60°C to 80°C for about 12 hours in order to stabilize the shape of the molded body. The shape of the expanded beads of the present invention can be stabilized, for example, by leaving the molded body after release in a high-temperature environment of about 60°C to 80°C for about 2 hours. In addition, obtaining a molded body by shortening the curing time in the in-mold molding of expanded beads as described above is also called short-time curing molding.

[0012] [Foam core layer] The expanded polypropylene resin particles of the present invention have an expanded core layer composed of a polypropylene resin. The expanded core layer of the polypropylene resin expanded particles (hereinafter, simply referred to as the expanded core layer) is made of a polypropylene resin and is in an expanded state. The polypropylene resin refers to a homopolymer of a propylene monomer and a propylene copolymer containing 50% by mass or more of structural units derived from propylene.

[0013] <Polypropylene resin> In the expanded polypropylene resin beads of the present invention, the polypropylene resin constituting the expanded core layer satisfies the following (i) or (ii). That is, the polypropylene-based resin constituting the foamed core layer is either a polypropylene-based resin that satisfies the following (i), a polypropylene-based resin that satisfies the following (ii), or a mixed resin of a polypropylene-based resin that satisfies the following (i) and a polypropylene-based resin that satisfies the following (ii). (i) the polypropylene-based resin constituting the foamed core layer is an ethylene-butene-propylene copolymer i, and the total amount Ccmt of the ethylene component and the butene component in the copolymer i (i)is 3.5 mass% or more (ii) the polypropylene-based resin constituting the foamed core layer is one or more copolymers ii selected from an ethylene-propylene copolymer and a butene-propylene copolymer, and the total amount Ccmt of the ethylene component and the butene component in the copolymer ii (ii) is 4.0 mass% or more The "total amount of ethylene components and butene components in the copolymer" refers to the "total (mass%) of the content (mass%) of the ethylene-derived component and the content (mass%) of the butene-derived component relative to the total mass of the copolymer." However, when the copolymer contains only one of the ethylene-derived component and the butene-derived component, the total amount of the ethylene component and the butene component in the copolymer means the content (mass%) of the one component. In this way, the foamed core layer is made of a polypropylene-based resin having a high ratio of monomers other than propylene, which enhances the secondary foaming property of the foamed core layer and provides excellent low-pressure moldability. Furthermore, the amount of steam required for in-mold molding is reduced, so that the obtained molded body tends to have stable dimensions even after short curing.

[0014] The polypropylene resin constituting the foamed core layer is preferably a resin polymerized using a Ziegler-Natta polymerization catalyst. When the polypropylene resin constituting the foamed core layer is a resin polymerized using a Ziegler-Natta polymerization catalyst, the formability is more likely to be expressed stably, especially during short-term curing. This is because the resin has a broader molecular weight distribution and contains a relatively large amount of low molecular weight components compared to resins polymerized using, for example, metallocene polymerization catalysts, and the low molecular weight components melt early during molding in the mold, improving fusion properties, and the dimensions are more likely to be stable even during short-term curing.

[0015] (Ethylene-butene-propylene copolymer i) The polypropylene-based resin is preferably a polypropylene-based resin that satisfies the above (i) out of the above (i) and (ii). That is, the polypropylene-based resin is preferably composed mainly of ethylene-butene-propylene copolymer i. Specifically, the mass ratio of ethylene-butene-propylene copolymer i in the polypropylene-based resin constituting the foamed core layer is preferably 60 mass% or more, more preferably 80 mass% or more. When the polypropylene-based resin is ethylene-butene-propylene copolymer i, the adhesion with the linear low-density polyethylene constituting the coating layer becomes better, and the effect of the present invention can be more stably exhibited. When the polypropylene resin constituting the foamed core layer is an ethylene-butene-propylene copolymer i, the total amount Ccmt of the ethylene component and the butene component in the copolymer i (i) is 3.5 mass % or more. The total amount Ccmt of the ethylene component and the butene component in the copolymer i (i) is 3.5% by mass or more, preferably 4.0% by mass or more, and more preferably 4.5% by mass or more. Also, it is preferably 8.0% by mass or less, more preferably 7.0% by mass or less, and even more preferably 6.0% by mass or less. And, it is preferably 3.5 to 8.0% by mass, more preferably 4.0 to 8.0% by mass, even more preferably 4.0 to 7.0% by mass, and even more preferably 4.5 to 6.0% by mass. By being composed of a polypropylene-based resin in which the total amount of the ethylene component and the butene component is within the above range, the secondary foaming property of the foamed core layer is enhanced, and the foamed core layer has excellent low-pressure moldability. Furthermore, the foaming property in a short time is also good. The mass ratio of the ethylene component to the butene component (ethylene / butene) in the copolymer i is preferably 50 / 50 to 98 / 2, more preferably 60 / 40 to 95 / 5, even more preferably 70 / 30 to 92 / 8, and still more preferably 80 / 20 to 90 / 10. When the mass ratio of the ethylene component to the butene component is within the above range, the adhesion to the linear low-density polyethylene constituting the coating layer becomes better.

[0016] (ii) One or more copolymers selected from ethylene-propylene copolymers and butene-propylene copolymers When the polypropylene-based resin constituting the foamed core layer is one or more copolymers ii selected from an ethylene-propylene copolymer and a butene-propylene copolymer, the total amount Ccmt of the ethylene component and the butene component in the copolymer ii is (ii) is 4.0 mass % or more. Of the copolymers ii, the polypropylene-based resin constituting the foamed core layer is preferably an ethylene-propylene copolymer, and may be a mixed resin of an ethylene-propylene copolymer and a butene-propylene copolymer. The total amount Ccmt of the ethylene component and the butene component in the copolymer ii (ii) is 4.0% by mass or more, preferably 4.2% by mass or more, and more preferably 4.5% by mass or more. Also, it is preferably 8.0% by mass or less, more preferably 7.0% by mass or less, and even more preferably 6.0% by mass or less. And, it is preferably 4.0 to 8.0% by mass, more preferably 4.0 to 7.0% by mass, even more preferably 4.2 to 6.0% by mass, and even more preferably 4.5 to 6.0% by mass. By being composed of a polypropylene-based resin in which the total amount of the ethylene component and the butene component is within the above range, the secondary foaming property of the foamed core layer is enhanced, and the foamed core layer has excellent low-pressure moldability. Furthermore, the foaming property in a short time is also good.

[0017] The one or more copolymers ii selected from the ethylene-butene-propylene copolymer i, ethylene-propylene copolymer, and butene-propylene copolymer constituting the foamed core layer may be a random copolymer or a block copolymer, and from the viewpoint of more reliably improving the moldability of the foamed beads, it is preferably a random copolymer.

[0018] The content of each monomer component in the copolymer means the content of the constituent units derived from each monomer in the copolymer. The content of these monomer components can be determined by IR spectrum measurement.

[0019] (Flexural modulus Mc) The flexural modulus Mc of the polypropylene resin constituting the foamed core layer is preferably 400 MPa or more, more preferably 500 MPa or more, and even more preferably 600 MPa or more, from the viewpoint of improving moldability at low pressure and shortening the curing time, and is preferably less than 800 MPa, more preferably 700 MPa or less, and even more preferably 650 MPa or less. That is, the flexural modulus Mc of the polypropylene resin constituting the foamed core layer is preferably 400 MPa or more and less than 800 MPa, more preferably 500 MPa or more and 700 MPa or less, and even more preferably 600 MPa or more and 650 MPa or less. By setting the flexural modulus Mc of the polypropylene resin constituting the foamed core layer in the above range, the low pressure moldability is excellent, and the dimensions can be stabilized by a short curing process. The flexural modulus Mc of polypropylene-based resins is determined based on JIS K 7171:2016.

[0020] Conventionally, when foamed beads made of polypropylene resin having a flexural modulus of less than 800 MPa are molded in a mold, the resistance to shrinkage and deformation after demolding is extremely small, so that when the curing time is set to a short time, the molded product tends to shrink and deform significantly. On the other hand, according to the above-mentioned foamed beads, even when foamed beads made of polypropylene resin having a flexural modulus of less than 800 MPa are used, the time required for the curing step can be shortened. This is because, as described later, the foamed beads have a foamed core layer made of a predetermined polypropylene resin, and also have a coating layer having a predetermined component and a predetermined mass ratio to the foamed core layer.

[0021] (Melting point Tmc) The melting point Tmc of the polypropylene resin constituting the foamed core layer is preferably 125° C. or higher, more preferably 128° C. or higher, even more preferably 130° C. or higher, and preferably 160° C. or lower, more preferably 150° C. or lower, even more preferably 145° C. or lower, and even more preferably 140° C. or lower, from the viewpoints of low pressure moldability, short time curing moldability, and mechanical properties of the molded body. That is, the melting point Tmc of the polypropylene resin constituting the foamed core layer is preferably 125 to 160° C., more preferably 128 to 150° C., even more preferably 130 to 145° C., and even more preferably 130 to 140° C. The melting point of polypropylene resin is determined based on JIS K 7121:1987 by adjusting the condition of the test piece as follows: "(2) Measurement of melting temperature after a certain heat treatment." The condition-adjusted test piece is heated from 30°C to 200°C at a heating rate of 10°C / min to obtain a DSC curve, and the melting point is determined as the apex temperature of the melting peak associated with the melting of the resin on the DSC curve. The condition adjustment is performed under conditions of a heating rate and a cooling rate of 10°C / min. If multiple melting peaks appear on the DSC curve, the apex temperature of the melting peak with the largest area is regarded as the melting point.

[0022] (Melt Flow Rate (MFR)) From the viewpoint of improving foamability and improving low pressure moldability and short time foaming moldability, the MFR of the polypropylene resin constituting the foamed core layer is preferably 2 g / 10 min or more, more preferably 4 g / 10 min or more, even more preferably 5 g / 10 min or more, and preferably 15 g / 10 min or less, more preferably 12 g / 10 min or less, even more preferably 10 g / 10 min or less. That is, the MFR of the polypropylene resin constituting the foamed core layer is preferably 2 to 15 g / 10 min, more preferably 4 to 12 g / 10 min, even more preferably 5 to 10 g / 10 min. The MFR of polypropylene resins is measured in accordance with JIS K 7210-1:2014 at a temperature of 230°C and a load of 2.16 kg.

[0023] The foamed core layer may contain other polymers within a range that does not impair the intended effects of the present invention. Examples of other polymers include polypropylene-based resins that do not satisfy either (i) or (ii), other types of thermoplastic resins other than polypropylene-based resins, thermoplastic elastomers, etc. However, the content of the other polymers in the foamed core layer is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and even more preferably 1% by mass or less, and 0% by mass. In other words, it is preferable that the foamed core layer contains only polypropylene-based resins that satisfy (i) or (ii) as polymers.

[0024] The foamed core layer may contain an appropriate amount of additives, provided that the additives do not impair the effects of the present invention. Examples of additives that can be added to the foamed core layer include cell regulators, lubricants, flame retardants, flame retardant assistants, colorants, cell nucleating agents, plasticizers, antistatic agents, antioxidants, ultraviolet inhibitors, light stabilizers, conductive fillers, and antibacterial agents.

[0025] [Coating layer] The coating layer of the expanded polypropylene resin particles (hereinafter, simply referred to as the coating layer) is made of linear low-density polyethylene and covers the expanded core layer made of polypropylene resin. If the expanded particles do not have the above-mentioned coating layer or if the resin constituting the coating layer is, for example, a polypropylene resin, the amount of steam required for heat fusion increases excessively, and the effects of the present invention, such as low-pressure moldability and short-time curing moldability, cannot be sufficiently obtained. From the viewpoint of reliably achieving the intended effects of the present invention, the content of the linear low-density polyethylene in the coating layer is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, still more preferably 80% by mass or more, and even more preferably 90% by mass or more. The proportion of the coating layer in the total surface area of ​​the expanded beads (the coverage of the foamed core layer by the coating layer) is preferably 50% or more, more preferably 60% or more, from the viewpoint of obtaining a sufficient effect of the coating layer. From the viewpoint of improving low pressure moldability and short-time curing moldability, the coating layer is preferably in a non-foamed state. Here, the non-foamed state includes not only a state in which no air bubbles are present in the coating layer, but also a substantially non-foamed state in which a small number of very small air bubbles are present. The state in which no air bubbles are present in the coating layer also includes a state in which air bubbles that were once formed are broken and disappear.

[0026] <Linear low density polyethylene (PE-LLD)> The coating layer is made of linear low-density polyethylene (PE-LLD). Linear low-density polyethylene is a copolymer of ethylene and α-olefin, which has a linear shape. The number of carbon atoms of the α-olefin constituting the copolymer is usually 4 to 10. By making the coating layer of linear low-density polyethylene, it is possible to improve the low-pressure moldability and the moldability during short-term curing. This is considered to be because the linear low-density polyethylene can improve the fusion between the foamed particles. In addition, one of the reasons is that the melting point of linear low-density polyethylene is in a moderate range and has moderate crystallinity. If the resin constituting the coating layer is a polyethylene-based resin other than linear low-density polyethylene, for example, high-density polyethylene (PE-HD), there is a risk that the low-pressure moldability will be impaired and that dimensional change will not be suppressed if the curing time is short. In addition, if the resin constituting the coating layer is low-density polyethylene (PE-LD), there is a risk that dimensional change will not be suppressed if the curing time is short.

[0027] (Heat of fusion) The heat of fusion of the PE-LLD constituting the coating layer is preferably 95 J / g or more and 130 J / g or less, more preferably 98 J / g or more and 120 J / g or less, and even more preferably 100 J / g or more and 110 J / g or less, from the viewpoint of short-term hardening and formability. The heat of fusion of PE-LLD is determined based on JIS K 7122:1987 by adjusting the condition of the test specimen as described in "(2) Measurement of heat of fusion after a certain heat treatment" and by raising the temperature of the adjusted test specimen from 30°C to 200°C at a heating rate of 10°C / min to obtain a DSC curve, and is calculated as the area of ​​the melting peak associated with the melting of the resin on the DSC curve. Note that when multiple melting peaks appear on the DSC curve, the heat of fusion calculated from the area of ​​the largest melting peak is regarded as the heat of fusion of PE-LLD.

[0028] (crystallization temperature) The crystallization temperature of the PE-LLD constituting the coating layer is preferably 100°C or higher and 115°C or lower, more preferably 100°C or higher and 110°C or lower, and even more preferably 102°C or higher and 108°C or lower, from the viewpoint of short-term cure and formability. The crystallization temperature of PE-LLD can be determined based on JIS K 7121:1987. Specifically, a test piece is heated from 23°C to 200°C at a heating rate of 10°C / min, and then kept at 200°C for 10 minutes, and then cooled to 30°C at a cooling rate of 10°C / min to obtain a DSC curve, and the crystallization temperature is determined as the apex temperature of the exothermic peak associated with the crystallization of the resin on the DSC curve. When multiple exothermic peaks appear on the DSC curve, the apex temperature of the exothermic peak with the largest area is taken as the crystallization temperature.

[0029] (density) The density of the linear low density polyethylene (PE-LLD) constituting the coating layer is preferably 0.900 g / cm from the viewpoints of low pressure moldability and short-time curing moldability. 3 More preferably, it is 0.905 g / cm 3 More preferably, it is 0.910 g / cm 3 and preferably 0.940 g / cm 3 More preferably, it is 0.930 g / cm or less. 3 More preferably, it is 0.920 g / cm or less. 3 The following is the result. The density of PE-LLD is measured, for example, in accordance with Method B (pycnometer method) described in JIS K 7112:1999.

[0030] (Melting point Tms) The melting point Tms of the PE-LLD constituting the coating layer is preferably 105°C or higher, more preferably 110°C or higher, and even more preferably 115°C or higher, from the viewpoints of low pressure moldability and short-time hardening moldability. The melting point Tms of the PE-LLD constituting the coating layer is preferably 128°C or lower, more preferably 125°C or lower, and even more preferably 122°C or lower. From the above viewpoints, the melting point Tms of the PE-LLD constituting the coating layer is preferably 105 to 128°C, more preferably 110 to 125°C, and even more preferably 115 to 122°C. The melting point Tms of PE-LLD is determined based on JIS K 7121:1987 by adjusting the condition of the test specimen as described in "(2) Measuring the melting temperature after a certain heat treatment" and obtaining a DSC curve by heating the adjusted test specimen from 30°C to 200°C at a heating rate of 10°C / min, and is determined as the apex temperature of the melting peak associated with the melting of the resin on the DSC curve. Note that when multiple melting peaks appear on the DSC curve, the apex temperature of the melting peak with the largest area is regarded as the melting point.

[0031] It is preferable that the melting point Tms (°C) of the linear low-density polyethylene constituting the coating layer is lower than the melting point Tmc (°C) of the polypropylene-based resin constituting the foamed core layer. That is, it is preferable that Tms < Tmc. In this case, the moldability of the expanded particles is improved, and in particular, the moldability at low pressure can be improved. From such a viewpoint, it is preferable that Tmc - Tms ≥ 3, more preferably Tmc - Tms ≥ 5, and still more preferably Tmc - Tms ≥ 10. On the other hand, from the viewpoint of suppressing peeling between the foamed core layer and the coating layer and mutual adhesion between the expanded particles during the production of the expanded particles, it is preferable that Tmc - Tms ≤ 35, more preferably Tmc - Tms ≤ 25, and still more preferably Tmc - Tms ≤ 20. From the above viewpoints, Tmc - Tms is preferably from 3 to 35°C, more preferably from 5 to 25°C, and still more preferably from 10 to 20°C.

[0032] The linear low-density polyethylene constituting the coating layer is preferably a resin polymerized using a Ziegler-Natta polymerization catalyst. When the linear low-density polyethylene constituting the coating layer is a resin polymerized using a Ziegler-Natta polymerization catalyst, the short-time curing moldability is particularly likely to be more stably exhibited. This is considered because this resin has a wider molecular weight distribution and relatively more low-molecular-weight components compared to, for example, a resin polymerized using a metallocene polymerization catalyst, and the low-molecular-weight components melt early during in-mold molding, improving the fusion property, and the dimensions are likely to be stable even with short-time curing.

[0033] According to the above expanded particles, the adhesiveness between the foamed core layer and the coating layer composed of linear low-density polyethylene polymerized using a Ziegler-Natta polymerization catalyst is excellent. This is because the foamed core layer is composed of a polypropylene-based resin that satisfies the above (i) or (ii), has a large amount of copolymer components, and in the process of laminating the coating layer on the core layer by coextrusion described later, it is difficult for molecular chains to be excluded at the interface between the core layer and the coating layer, and components compatible with the ethylene component of the coating layer are sufficiently present in the core layer, etc. are considered as reasons. The excellent adhesive layer between the foamed core layer and the covering layer prevents the foamed core layer from peeling off from the interface with the covering layer when the foamed bead molding is folded, so that a molding having excellent fusion properties can be stably obtained at a molding pressure expected from the configuration of the foamed core layer and the covering layer of the foamed beads. Therefore, the foamed beads having the above configuration can be molded more easily at low pressure, and the effect of short-term curing formability is more stably exhibited.

[0034] In the past, in expanded beads having a foamed core layer made of a polypropylene resin and a coating layer made of linear low-density polyethylene that coats the foamed core layer, a resin polymerized using a metallocene polymerization catalyst has been suitably used as the linear low-density polyethylene that constitutes the coating layer from the viewpoint of excellent adhesion between the foamed core layer and the coating layer. On the other hand, the above-mentioned expanded beads have excellent adhesion between the foamed core layer and the coating layer even when a resin polymerized using a Ziegler-Natta polymerization catalyst is used as the linear low-density polyethylene that constitutes the coating layer. Therefore, as described above, the foamed beads are more likely to exhibit shapeability, particularly in a short time, more stably.

[0035] (Flexural modulus Ms) The flexural modulus Ms of the PE-LLD constituting the coating layer is preferably 120 MPa or more. In this case, the sliding property and toughness of the molded body can be further improved. From this viewpoint, the flexural modulus Ms of the PE-LLD constituting the coating layer is more preferably 150 MPa or more, even more preferably 180 MPa or more, and particularly preferably 200 MPa or more. On the other hand, the flexural modulus Ms of the PE-LLD constituting the coating layer is preferably 600 MPa or less. In this case, the moldability of the expanded beads and the toughness of the obtained molded body can be further improved. From this viewpoint, the flexural modulus Ms of the PE-LLD constituting the coating layer is more preferably 500 MPa or less, even more preferably 400 MPa or less, particularly preferably 300 MPa or less, and most preferably 250 MPa or less. From the above viewpoint, the flexural modulus Ms of the PE-LLD constituting the coating layer is preferably 120 to 600 MPa, more preferably 150 to 500 MPa, even more preferably 180 to 400 MPa, even more preferably 200 to 300 MPa, and even more preferably 200 to 250 MPa. The flexural modulus Ms of PE-LLD is determined based on JIS K 7171:2016.

[0036] (Melt Flow Rate (MFR)) The melt flow rate (MFR) of the PE-LLD constituting the coating layer is preferably 0.5 to 5.0 g / 10 min, more preferably 1.0 to 3.5 g / 10 min, and even more preferably 1.5 to 2.5 g / 10 min, from the viewpoint of more easily producing expanded beads having excellent filling ability, for example, an aspect ratio of 0.8 to 1.3, and from the viewpoint of improving the coverage of the foamed core layer by the coating layer and more stably achieving the intended effects of the present application. The MFR of PE-LLD is measured in accordance with JIS K 7210-1:2014 at a temperature of 190°C and a load of 2.16 kg.

[0037] The coating layer may contain a polyethylene resin other than linear low-density polyethylene, such as low-density polyethylene, high-density polyethylene, etc. However, from the viewpoint of further improving the effect of the linear low-density polyethylene, the ratio of linear low-density polyethylene in the resin constituting the coating layer is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass, that is, the resin constituting the coating layer contains only linear low-density polyethylene as a polymer.

[0038] The coating layer may appropriately contain other polymers and additives other than polyethylene-based resins, so long as the effects of the present invention are not impaired. Examples of the other polymers include thermoplastic resins such as polypropylene-based resins and polystyrene-based resins, and thermoplastic elastomers. The content of the other polymers in the coating layer is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less, based on the total mass of the coating layer. It is particularly preferable that the content of the other polymers in the coating layer is 0% by mass, that is, the coating layer contains only polyethylene-based resins as polymers. Examples of additives include bubble adjusters, lubricants, flame retardants, flame retardant assistants, colorants, bubble nucleating agents, plasticizers, antistatic agents, antioxidants, ultraviolet inhibitors, light stabilizers, conductive fillers, and antibacterial agents.

[0039] [Characteristics of polypropylene resin foam particles] The expanded polypropylene resin beads of the present invention are polypropylene resin beads having an expanded core layer made of a polypropylene resin and a coating layer coating the expanded core layer, the coating layer being made of linear low-density polyethylene, the mass ratio of the coating layer to the expanded core layer being 0.005 or more and 0.05 or less, and the polypropylene resin constituting the expanded core layer satisfying the above (i) or (ii). The expanded beads preferably further have the following characteristics.

[0040] <Mass ratio of foamed core layer to covering layer> The mass ratio of the coating layer to the foamed core layer [mass of the coating layer / mass of the foamed core layer] is 0.005 or more and 0.05 or less. If the mass ratio of the coating layer is too large, the molding pressure reduction effect is sufficient, but the formability during short-term curing is impaired, and in particular, when attempting to produce a molded body with a low apparent density, there is a risk that the dimensional change of the molded body cannot be suppressed when the curing time is set short. In other words, a long-term curing process is required. From the viewpoint of further suppressing significant shrinkage and deformation of the molded body after molding in the mold, the mass ratio of the coating layer to the foamed core layer is preferably 0.045 or less, more preferably 0.04 or less, and even more preferably 0.035 or less. On the other hand, if the mass ratio of the coating layer is too small, the molding pressure reduction effect of the coating layer is not fully exhibited, and there is a risk that significant shrinkage and deformation cannot be suppressed when the curing time is shortened. From the viewpoint of suppressing shrinkage and deformation even when the curing time is shortened, the mass ratio of the coating layer to the foamed core layer is preferably 0.01 or more, more preferably 0.015 or more, and even more preferably 0.02 or more. The mass ratio of the coating layer to the foamed core layer is preferably 0.01 or more and 0.045 or less, more preferably 0.015 or more and 0.04 or less, and even more preferably 0.02 or more and 0.035 or less. The mass ratio of the foamed core layer to the coating layer in the expanded beads corresponds to the mass ratio of the core layer to the coating layer in the multilayer resin beads described later.

[0041] As described above, the reason why the shrinkage and deformation of the molded body can be easily suppressed by adjusting the mass ratio of the coating layer even when the curing time is shortened is considered to be as follows. In order to reduce the weight of the molded body, expanded beads with a small apparent density are usually used for in-mold molding. In addition, the coating layer of the expanded beads is usually composed of, for example, a substantially non-expanded resin. Therefore, when the mass ratio of the coating layer is large, it is necessary to make the apparent density of the expanded core layer smaller in order to reduce the apparent density of the entire expanded beads. As a result, it is considered that the resistance to shrinkage and deformation of the molded body after demolding is likely to decrease. In addition, the coating layer is usually composed of linear low-density polyethylene, which usually has a lower melting point than the polypropylene-based resin that usually constitutes the foamed core layer. Therefore, when the mass ratio of the coating layer is large, it is considered that the expanded beads are easily affected by heat from steam during in-mold molding, and the entire expanded beads are likely to shrink. From the above, when the mass ratio of the coating layer is too large, particularly when attempting to produce a molded article with a low apparent density, it is considered that although the molding pressure of the expanded beads can be reduced, it becomes difficult to suppress significant shrinkage and deformation of the molded article in short-term curing forming. Therefore, the expanded beads of the present invention can achieve both low-pressure moldability and short-term curing formability at a high level by forming the foamed core layer from a specific polypropylene-based resin and forming the foamed core layer and the coating layer of linear low-density polyethylene in a specific mass ratio.

[0042] From the viewpoint of more reliably improving the formability during short-time curing, the average thickness (Tt) of the coating layer is preferably 5 μm or less, more preferably 4 μm or less, even more preferably 3.5 μm or less, and even more preferably 3 μm or less. Also, from the viewpoint of fully exerting the molding pressure reducing effect of the coating layer and more reliably suppressing significant shrinkage and deformation when the curing time is shortened, the average thickness (Tt) of the coating layer is preferably 0.1 μm or more, more preferably 0.3 μm or more, even more preferably 0.5 μm or more, and even more preferably 1 μm or more. From the above viewpoint, the average thickness (Tt) of the coating layer is preferably 0.1 μm or more and 5 μm or less, more preferably 0.3 μm or more and 4 μm or less, even more preferably 0.5 μm or more and 3.5 μm or less, and even more preferably 1 μm or more and 3 μm or less.

[0043] In this specification, the average thickness (Tt) of the coating layer is a value calculated using the following formulas (1), (2), and (3). Formulas (1) to (3) are derived as the average value (Tt) of the coating layer of expanded beads obtained by expanding cylindrical multilayer resin particles having a coating layer into a similar shape. However, even if the expanded beads of the present invention are obtained from multilayer resin particles having a shape other than cylindrical, the average thickness (Tt) of the coating layer is calculated using the following formulas (1), (2), and (3). The physical properties of the multilayer expanded beads used to calculate the average thickness (Tt) of the coating layer of the expanded beads are values ​​determined from a multilayer expanded particle group obtained by expanding a multilayer resin particle group having the physical properties of the multilayer resin particles used to calculate the average thickness (Tt).

[0044] Pd = {(4 × W) ÷ (π × Ld × Db)} (1 / 3) (1) where the diameter of the cylindrical multi-layer foamed particle is Pd [cm], the mass of the multi-layer resin particle is W [g], and the apparent density of the multi-layer foamed particle is Db [g / cm 3 ], and L / D of the resulting expanded beads is Ld.

[0045] Cd={Pd 2 - (4×R×W)÷(π×Pd×Ld×ρ)} (1 / 2) (2) where Cd [cm] is the diameter of only the core layer of the cylindrical multilayer foamed particle, R (dimensionless) is the mass ratio of the resin in the coating layer of the multilayer resin particle (mass of resin in coating layer (S) / (mass of resin in coating layer (S) + mass of resin in core layer (C)) and ρ [g / cm 3 ].

[0046] Tt[μm]={(Pd-Cd)÷2}×10000...(3)

[0047] The method for calculating the apparent density Db of the expanded beads is as follows. First, the expanded beads are left to stand for 24 hours in an environment of 50% relative humidity, 23°C temperature, and 1 atm atmospheric pressure to adjust the state of the expanded beads. After measuring the mass (unit: g) of the expanded beads, they are submerged in a measuring cylinder containing 23°C water using a wire net or the like, and the volume (unit: L) of the expanded beads is calculated from the rise in the liquid level. The apparent density (unit: g / cm) of the expanded beads is then calculated by converting the value obtained by dividing the mass of the expanded beads by the volume of the expanded beads. 3 ) can be calculated.

[0048] <Bulk magnification> The bulk ratio of the expanded polypropylene resin particles is preferably 45 times or less, more preferably 40 times or less, and even more preferably 35 times or less. On the other hand, the bulk ratio of the expanded polypropylene resin particles is preferably 5 times or more, more preferably 10 times or more, and even more preferably 20 times or more. From the above viewpoint, the bulk ratio of the expanded polypropylene resin particles is preferably 5 to 45 times, more preferably 10 to 40 times, and even more preferably 20 to 35 times. By having the bulk ratio of the expanded polypropylene resin particles in the above range, the effects of the present invention can be fully exhibited, low pressure moldability can be improved, and curing time can be shortened. The bulk ratio of the expanded beads is calculated as follows. First, the expanded beads are left to stand for 24 hours in an environment of 50% relative humidity, 23°C temperature, and 1 atm pressure to condition the expanded beads. After the condition is adjusted, expanded beads are randomly taken out of the expanded beads and placed in a measuring cylinder with a volume of 1 L. A large number of expanded beads are placed up to the 1 L mark so as to form a natural pile-up state. The mass W1 [g] of the expanded beads is divided by the volume V1 (1 [L]) (W1 / V1), and the bulk density [kg / m2] of the expanded beads is calculated by converting the unit. 3 The density [kg / m ] of the resin constituting the foamed core layer of the foamed beads is then calculated. 3 ] is the bulk density [kg / m 3 ] can be calculated by dividing by

[0049] <Average bubble diameter> From the viewpoint of further improving the moldability of the expanded beads, the average bubble diameter of the expanded polypropylene resin beads is preferably 80 μm or more, more preferably 100 μm or more, and even more preferably 150 μm or more. On the other hand, from the viewpoint of further improving the surface smoothness of the resulting expanded bead molding, the average bubble diameter of the expanded polypropylene resin beads is preferably 300 μm or less, more preferably 250 μm or less, and even more preferably 220 μm or less. From the above viewpoint, the average bubble diameter of the expanded polypropylene resin beads is preferably 80 to 300 μm, more preferably 100 to 250 μm, even more preferably 150 to 250 μm, and even more preferably 150 to 220 μm. The average bubble diameter of expanded beads is measured as follows. Twenty or more expanded beads are randomly selected from a group of expanded beads. Each expanded bead is cut through its center and divided into two, and an enlarged photograph of the entire cross section of each is taken using a microscope such as a scanning electron microscope. In each cross-sectional photograph, four lines are drawn at an equal angle (45°) from the outermost surface of the expanded bead through the center to the outermost surface on the opposite side. The number of bubbles intersecting each line is counted, and the total length of the four lines is divided by the total number of bubbles intersecting the lines to determine the bubble diameter of each expanded bead. The value obtained by arithmetically averaging these values ​​is taken as the average bubble diameter of the expanded beads.

[0050] <Closed bubble rate> The closed cell ratio of the expanded beads is preferably 85% or more, more preferably 90% or more, and even more preferably 95% or more. In this case, the moldability of the expanded beads and the rigidity of the resulting expanded bead molding can be further improved. The closed cell ratio of the expanded beads can be measured using an air comparison type specific gravity meter based on ASTM D2856-70.

[0051] <High temperature peak> The expanded beads preferably have a crystal structure in which, in a DSC curve obtained by heating the expanded beads from 23°C to 200°C at a heating rate of 10°C / min by heat flux differential scanning calorimetry (DSC), one or more endothermic peaks (hereinafter referred to as "high-temperature peaks") appear on the high-temperature side of the apex of an endothermic peak (hereinafter referred to as "intrinsic peak") inherent to the polypropylene resin constituting the core layer. In this case, the moldability of the expanded beads can be further improved, and the rigidity of the resulting expanded bead molding can be further increased. From this viewpoint, the heat of fusion of the high-temperature peak is preferably 5 to 50 J / g, more preferably 8 to 40 J / g, and even more preferably 10 to 30 J / g.

[0052] <Other characteristics> The expanded beads are not particularly limited, but may have a columnar shape, such as a cylindrical shape. The aspect ratio L / D of the expanded polypropylene resin particles is preferably 0.8 to 1.4 in terms of improving the filling property of the expanded particles and improving the rigidity of the molded article, more preferably 0.9 to 1.3, and even more preferably more than 0.9 and less than 1.3. The aspect ratio L / D of the expanded beads is determined by measuring with a vernier caliper the maximum axial length (L) of the expanded beads and the maximum cross-sectional diameter (D) of the cross-section of the beads in a direction perpendicular to the longitudinal direction of the maximum length for 100 randomly selected expanded beads, calculating the ratio (L / D), and then arithmetically averaging the values. In order to further improve the appearance of the resulting molded article, it is preferable that the expanded beads have no through holes.

[0053] [Method of manufacturing polypropylene resin foam particles] The expanded polypropylene-based resin beads of the present invention are polypropylene-based resin beads having an expanded core layer composed of a polypropylene-based resin and a coating layer coating the expanded core layer, wherein the coating layer is composed of linear low-density polyethylene, the mass ratio of the coating layer to the expanded core layer is 0.005 or more and 0.05 or less, and the polypropylene-based resin constituting the expanded core layer satisfies the above (i) or (ii). There are no limitations on the manufacturing method, but it is preferable to manufacture the expanded polypropylene-based resin beads by the method shown below.

[0054] A preferred method for producing the expanded polypropylene resin beads of the present invention includes the following steps (A) to (C). Step (A): A dispersion step of dispersing, in a sealed container, multilayer resin particles having a core layer made of a polypropylene-based resin and in a non-foamed state, and a coating layer made of linear low-density polyethylene and coating the core layer, in a dispersion medium; Step (B): A foaming agent impregnation step of impregnating the multilayer resin particles with a foaming agent; and Step (C): An expansion step in which the expandable multilayer resin particles impregnated with a blowing agent are released from the sealed container together with a dispersion medium into an atmosphere having a lower pressure than the pressure inside the sealed container, thereby expanding at least the core layer into a foamed core layer, thereby producing foamed particles. The order of steps (A) and (B) does not matter, and they may be performed simultaneously, but from the viewpoint of efficient production, it is preferable to perform step (B) after step (A).

[0055] <Multi-layered resin particles and method for producing multi-layered resin particles> The multilayer resin particles used in step (A) are multilayer resin particles having a core layer made of a polypropylene resin and in a non-foamed state, and a coating layer made of linear low-density polyethylene and coating the core layer. The multilayer resin particles used in step (A) are preferably multilayer resin particles having a cylindrical core layer made of a polypropylene resin and in a non-foamed state, and a coating layer made of linear low-density polyethylene and laminated on the lateral surface of the core layer by coextrusion to coat the core layer.

[0056] The method for producing multilayer resin particles can use, for example, an extruder having a core layer forming extruder, a coating layer forming extruder, and a multilayer strand forming co-extrusion die installed on the outlet side of these extruders. The core layer forming extruder is supplied with a polypropylene resin constituting the core layer and additives added as necessary, and melt-kneaded to form a core layer forming melt kneaded material, and the coating layer forming extruder is supplied with a linear low-density polyethylene constituting the coating layer and additives added as necessary, and melt-kneaded to form a coating layer forming melt kneaded material. The core layer forming melt kneaded material and the coating layer forming melt kneaded material are introduced into the multilayer strand forming co-extrusion die and merged to form a composite having a core-sheath structure, which is composed of a non-foamed core layer and a non-foamed coating layer covering the side peripheral surface of the core layer. The composite is extruded in the form of a strand from a small hole in a die attached to the tip of the extruder, cooled in water, and then cut to a predetermined mass with a pelletizer (strand cut method), thereby obtaining multilayer resin particles having a non-foamed core layer and a coating layer that coats the core layer. In addition to the above-mentioned method, the extruded composite can also be cut by an underwater cut method in which the composite is extruded into water and cut, or a hot cut method in which the composite is extruded into air and cut immediately afterwards.

[0057] The particle size of the multilayered resin particles is preferably 0.1 to 5.0 mm, and more preferably 0.5 to 3.0 mm.

[0058] The mass of the multilayer resin particles is adjusted to be preferably 0.1 to 20 mg, more preferably 0.2 to 10 mg, even more preferably 0.3 to 5 mg, and even more preferably 0.4 to 2 mg. The mass of the multilayer resin particles is calculated by dividing the total mass of 100 randomly selected multilayer resin particles by 100.

[0059] The mass ratio of the coating layer to the expanded core layer of the expanded beads can be adjusted by the mass ratio of the coating layer to the non-expanded core layer of the multilayer resin particles. From this viewpoint, the mass ratio of the coating layer to the core layer of the multilayer resin particles is 0.005 or more and 0.05 or less, preferably 0.01 or more and 0.045 or less, more preferably 0.015 or more and 0.04 or less, and even more preferably 0.02 or more and 0.035 or less.

[0060] Additives such as bubble regulators, flame retardants, flame retardant auxiliaries, bubble nucleating agents, plasticizers, antistatic agents, antioxidants, UV inhibitors, light stabilizers, conductive fillers, and antibacterial agents can be added to the multilayer resin particles having a non-foamed core layer and a coating layer, as necessary. When additives are added, they can be added in step (A). Examples of bubble regulators include inorganic powders such as talc, mica, zinc borate, calcium carbonate, silica, titanium oxide, gypsum, zeolite, borax, aluminum hydroxide, and carbon; and organic powders such as phosphoric acid-based nucleating agents, phenol-based nucleating agents, amine-based nucleating agents, and polyethylene fluoride-based resin powder. When a bubble regulator is added, the content of the bubble regulator is preferably 0.01 to 1 part by mass with respect to 100 parts by mass of the polymer constituting the core layer of the multilayer resin particles.

[0061] The particle size and average mass of the multilayer resin particles can be adjusted by appropriately changing the resin discharge speed, take-up speed, cutter speed, etc., during cutting in the strand cut method.

[0062] <Process (A)> In the step (A), the multilayered resin particles can be dispersed in a dispersion medium using, for example, a stirrer in a container that is sealable and can withstand heat and pressure, such as an autoclave.

[0063] The dispersion medium is not particularly limited as long as it does not dissolve the multilayer resin particles. Examples of the dispersion medium include water, ethylene glycol, glycerin, and alcohols such as methanol and ethanol, and among these, water is preferred.

[0064] In step (A), in order to prevent the multilayer resin particles from fusing together, it is preferable to further add a dispersant to the dispersion medium. Examples of the dispersant include organic dispersants such as polyvinyl alcohol, polyvinylpyrrolidone, and methyl cellulose; and poorly soluble inorganic salts such as aluminum oxide, zinc oxide, kaolin, mica, magnesium phosphate, and tricalcium phosphate. These can be used alone or in combination of two or more. Among these, from the viewpoint of ease of handling, poorly soluble inorganic salts are preferable, and kaolin is more preferable. When a dispersant is added, the amount of the dispersant added is preferably 0.001 to 5 parts by mass relative to 100 parts by mass of the multilayer resin particles.

[0065] A surfactant may be further added to the dispersion medium. Examples of the surfactant include sodium dodecylbenzenesulfonate, sodium alkylsulfonate, sodium oleate, sodium lauryl sulfate, sodium polyoxyethylene alkyl ether phosphate, sodium polyoxyethylene alkyl ether sulfate, and other anionic surfactants and nonionic surfactants that are generally used in suspension polymerization. When a surfactant is added, the amount of the surfactant added is preferably 0.001 to 1 part by mass relative to 100 parts by mass of the multilayer resin particles.

[0066] <Process (B)> In step (B), for example, the resin is heated to a temperature equal to or higher than the softening temperature of the polypropylene resin constituting the core layer, and impregnated with a foaming agent to obtain expandable multilayer resin particles.

[0067] The foaming agent is not particularly limited as long as it can foam the multilayer resin particles. Examples of the foaming agent include inorganic physical foaming agents such as air, nitrogen, carbon dioxide, argon, helium, oxygen, and neon, aliphatic hydrocarbons such as propane, normal butane, isobutane, normal pentane, isopentane, and normal hexane, alicyclic hydrocarbons such as cyclohexane and cyclopentane, halogenated hydrocarbons such as chlorofluoromethane, trifluoromethane, 1,1-difluoroethane, 1,1,1,2-tetrafluoroethane, methyl chloride, ethyl chloride, and methylene chloride, and organic physical foaming agents such as dialkyl ethers such as dimethyl ether, diethyl ether, and methyl ethyl ether. Among these, inorganic physical foaming agents that do not destroy the ozone layer and are inexpensive are preferred, and nitrogen, air, and carbon dioxide are more preferred, and carbon dioxide is even more preferred. These may be used alone or in combination of two or more kinds.

[0068] The amount of foaming agent added is determined taking into consideration the desired bulk density of the expanded particles, the type of polypropylene resin, the type of foaming agent, etc., but in the case of an organic physical foaming agent, the amount of foaming agent added is preferably 5 to 50 parts by mass per 100 parts by mass of the multilayer resin particles, and in the case of an inorganic physical foaming agent, the amount of foaming agent added is preferably 0.1 to 30 parts by mass, and more preferably 0.5 to 15 parts by mass, per 100 parts by mass of the multilayer resin particles.

[0069] The heating temperature in step (B) is preferably equal to or higher than the melting point of the polypropylene resin and equal to or lower than the melting point + 80° C., specifically, preferably 100° C. to 230° C. The time for which the material is held at the heating temperature is preferably 1 minute or more, more preferably 20 minutes or more, and preferably 100 minutes or less, more preferably 60 minutes or less. That is, the time for which the material is held at the heating temperature is preferably 1 to 100 minutes, more preferably 20 to 60 minutes.

[0070] <Process (C)> In step (C), for example, the expandable multilayer resin particles that have been impregnated with a blowing agent in step (B) and that have been heated are released from the sealed container into an atmosphere having a pressure lower than the pressure inside the sealed container, and at least the core layer is expanded to form a foamed core layer, thereby producing expanded particles. Specifically, while maintaining the pressure in the sealed container at or above the vapor pressure of the blowing agent, one end of the sealed container below the water surface is opened, and the expandable multilayer resin particles impregnated with the blowing agent are released from the sealed container together with the dispersion medium into an atmosphere of a lower pressure than the pressure in the sealed container, usually atmospheric pressure, and at least the core layer of the expandable multilayer resin particles is expanded to form a foamed core layer, thereby producing expanded beads of a multilayer structure having a foamed core layer and a coating layer that covers the foamed core layer.Furthermore, the expandable multilayer resin particles that have been subjected to step (B) can also be produced by cooling and removing them, and then heating the expandable multilayer resin particles with a heating medium such as hot air or steam to expand them.

[0071] In step (C), the temperature during foaming is preferably 110° C. to 170° C. The pressure inside the sealed container is preferably 0.5 MPa (G) or more and 5 MPa (G) or less. Here, "0.5 MPa (G)" means that the gauge pressure is 0.5 MPa.

[0072] The above steps (A) to (C) are preferably carried out as a series of steps in a single sealed container. However, they can also be separate steps in which the multilayer resin particles or the like are removed for each step and then re-inserted into the sealed container to carry out the next step.

[0073] In the above process, it is preferable to carry out a first-stage holding step in which the temperature is held at a temperature of (melting point of polypropylene resin constituting the core layer -20°C) or more and (end of melting of polypropylene resin constituting the core layer) for a sufficient time, preferably about 10 to 60 minutes, during heating in a closed container. Furthermore, it is preferable to carry out a second-stage holding step in which the temperature is adjusted to (melting point of the polypropylene resin -15°C) to (end of melting of the polypropylene resin +10°C) and, if necessary, held at that temperature for a further sufficient time, preferably 10 to 60 minutes. Thereafter, the expandable resin particles containing a foaming agent are released from the closed container under low pressure and expanded to obtain expanded particles having a crystal structure that shows the above-mentioned high-temperature peak.

[0074] The expanded beads obtained as described above can be pressurized with an inorganic gas such as air to increase the internal pressure, and then heated with steam or the like to expand (two-stage expansion) to give expanded beads with a higher expansion ratio (lower apparent density).

[0075] <Production of foamed bead molded body> Expanded bead moldings can be obtained by molding expanded beads in a mold. By using the expanded polypropylene resin beads of the present invention, the steam pressure during molding in a mold can be significantly reduced, and even if the curing time is shortened, an expanded bead molding having the desired shape and excellent appearance can be obtained. The in-mold molding of the expanded beads can be carried out by filling the expanded beads in a mold and molding them by heating using a heating medium such as steam. Specifically, after filling the expanded beads in the mold, a heating medium such as steam is introduced into the mold to heat the expanded beads to perform secondary expansion, and the surfaces are melted and fused together to obtain an expanded bead molded body having the shape of the molding space. It is also preferable to perform molding by a pressure molding method (for example, JP-B-51-22951) in which the expanded beads are pressurized in advance with a pressurized gas such as air to increase the pressure in the bubbles of the expanded beads and adjust the pressure in the expanded beads to a pressure 0.01 to 0.3 MPa higher than atmospheric pressure, and then the expanded beads are filled in the mold under atmospheric pressure or reduced pressure, and then a heating medium such as steam is supplied into the mold to heat and fuse the expanded beads. Molding can also be performed by a compression filling molding method (JP-B-4-46217) in which a mold pressurized to atmospheric pressure or higher by a compressed gas is filled with expanded beads, which have been pressurized to the atmospheric pressure or higher, and then a heating medium such as steam is supplied into the cavity to heat and fuse the expanded beads. Molding can also be performed by a normal pressure filling molding method (JP-B-6-49795) in which expanded beads with high secondary expansion power obtained under special conditions are filled into the cavity of a mold under atmospheric pressure or reduced pressure, and then a heating medium such as steam is supplied to heat and fuse the expanded beads, or a combination of the above methods (JP-B-6-22919). EXAMPLES

[0076] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0077] The resins and expanded beads used in the examples and comparative examples were subjected to the following measurements and evaluations. The expanded beads were conditioned by being left to stand for 24 hours under conditions of 50% relative humidity, 23°C, and 1 atm.

[0078] [Measurement and Evaluation] <Raw material resin> (Monomer content of polypropylene resin) The monomer content of polypropylene resin (specifically, ethylene-propylene copolymer, ethylene-propylene-butene copolymer) was determined by a known method determined by IR spectrum. Specifically, it was determined by the method described in Polymer Analysis Handbook (edited by Polymer Analysis Research Forum, Japan Analytical Chemistry Society, published in January 1995, publisher: Kinokuniya Shoten, page numbers and item names: 615-616 "II.2.3 2.3.4 Propylene / ethylene copolymer", 618-619 "II.2.3 2.3.5 Propylene / butene copolymer"), that is, by a method of quantitatively determining the relationship between the value of the absorbance of the ethylene component and the butene component corrected by a predetermined coefficient and the thickness of the film-like test piece, etc.

[0079] More specifically, first, a polypropylene-based resin was hot-pressed in an environment of 180°C to form a film, and a number of test pieces with different thicknesses were prepared. Next, the IR spectrum of each test piece was measured to find the 722 cm -1 and 733 cm -1 Absorbance at (A 722 , A 733 ) and 766 cm -1 Absorbance at (A 766 ) was read. Next, for each test piece, the ethylene component content (unit: mass%) in the polypropylene-based resin was calculated using the following formulas (4) to (6). The arithmetic average of the ethylene component contents obtained for each test piece was taken as the ethylene component content (unit: mass%) in the polypropylene-based resin.

[0080] (K' 733 ) c =1 / 0.96{(K' 733 ) a -0.268(K' 722 ) a}···(4) (K' 722 ) c =1 / 0.96{(K' 722 ) a -0.150(K' 733 ) a}···(5) Ethylene content = 0.575 {(K' 722 ) c +(K' 733 ) c}···(6)

[0081] However, K' in formulas (4) to (6) a is the apparent extinction coefficient at each wave number (K' a =A / ρt) and K' c is the corrected extinction coefficient, A is the absorbance, and ρ is the density of the resin (unit: g / cm 3 ) and t is the thickness (unit: cm) of the film-like test piece. The above formulas (4) to (6) can be applied to random copolymers.

[0082] In addition, for each test piece, the butene component content (unit: mass%) in the polypropylene-based resin was calculated using the following formula (7). The arithmetic average of the butene component contents obtained for each test piece was taken as the butene component content (unit: mass%) in the polypropylene-based resin. Butene content = 12.3 (A 766 / L) · · · (7) In the formula (7), A is the absorbance, and L is the thickness of the film-like test piece (unit: mm).

[0083] (Flexural modulus) The flexural modulus of the resin was measured by the following method. First, the resin was heat pressed at 230°C to produce a 4 mm sheet, and a test piece with a length of 80 mm, width of 10 mm, and thickness of 4 mm was cut out from this sheet. The flexural modulus of this test piece was determined in accordance with JIS K 7171:2016. The radius R1 of the indenter and the radius R2 of the support table were both 5 mm, the distance between the supports was 64 mm, and the test speed was 2 mm / min.

[0084] (MFR) The MFR of the resin was measured at a temperature of 190°C or 230°C under a load of 2.16 kg in accordance with JIS K 7210-1:2014. A temperature of 230°C was used to measure the MFR of polypropylene resin, and a temperature of 190°C was used to measure the MFR of linear low-density polyethylene.

[0085] (Melting point (Tm)) The melting point of the resin was measured based on JIS K 7121:1987. Specifically, "(2) A case where the melting temperature is measured after a certain heat treatment" was adopted, and the condition of the test piece was adjusted under the condition of a heating rate and a cooling rate of 10°C / min. The condition-adjusted test piece was heated from 30°C to 200°C at a heating rate of 10°C / min to obtain a DSC curve, and the melting point was determined as the apex temperature of the melting peak associated with the melting of the resin on the DSC curve. When multiple melting peaks appear on the DSC curve, the apex temperature of the melting peak with the largest area was determined as the melting point. The measurement device used was a heat flux differential scanning calorimeter (manufactured by SII Nanotechnology Co., Ltd., model number: DSC7020).

[0086] (density) The density of the resin was measured in accordance with the B method (pycnometer method) described in JIS K 7112:1999. The density of the polypropylene resin used in the present invention was 900 kg / m 3 It is.

[0087] (Heat of fusion) The heat of fusion of linear low-density polyethylene was measured based on JIS K 7122:1987, and the condition of the test specimen was adjusted as follows: "(2) Measurement of heat of fusion after a certain heat treatment." The condition-adjusted test specimen was heated from 30°C to 200°C at a heating rate of 10°C / min to obtain a DSC curve, and the heat of fusion was calculated as the area of ​​the melting peak associated with the melting of the resin on the DSC curve. When multiple melting peaks appear on the DSC curve, the heat of fusion calculated from the area of ​​the largest melting peak was used as the heat of fusion of the linear low-density polyethylene. The measurement device used was a heat flux differential scanning calorimeter (manufactured by SII Nanotechnology Co., Ltd., model number: DSC7020).

[0088] (crystallization temperature) The crystallization temperature of linear low density polyethylene was determined based on JIS K 7121:1987. Specifically, a test piece was heated from 23°C to 200°C at a heating rate of 10°C / min, and after keeping the temperature at 200°C for 10 minutes, the test piece was cooled to 30°C at a cooling rate of 10°C / min to obtain a DSC curve, and the apex temperature of the exothermic peak associated with the crystallization of the resin on the DSC curve was taken as the crystallization temperature. When multiple exothermic peaks appear on the DSC curve, the apex temperature of the exothermic peak with the largest area was taken as the crystallization temperature. The measurement device used was a heat flux differential scanning calorimeter (manufactured by SII Nanotechnology Co., Ltd., model number: DSC7020).

[0089] <Expanded particles> (bulk magnification) The bulk ratio of the expanded beads was calculated as follows: Expanded beads were randomly taken from the expanded bead group and placed in a measuring cylinder with a volume of 1 L, and a large number of expanded beads were placed up to the 1 L mark so as to form a natural pile-up state. The mass W1 [g] of the expanded beads was divided by the volume V1 (1 [L]) to obtain the unit conversion (W1 / V1) to obtain the bulk density [kg / m 3 The density [kg / m 2 ] of the polypropylene resin constituting the foamed core layer of the foamed beads was then determined. 3 ] is the bulk density [kg / m 3 ] was calculated by dividing by

[0090] (High-temperature peak heat of fusion) The heat of fusion of the high-temperature peak of the expanded beads was determined as follows. Approximately 3 mg of expanded beads was collected and heated from 23°C to 200°C at a heating rate of 10°C / min using a differential scanning calorimeter (DSC Q1000 manufactured by TA Instruments), and a DSC curve was obtained having an endothermic peak (resin-specific peak) due to the melting specific to the polypropylene resin and one or more melting peaks (high-temperature peaks) on the high-temperature side. In the following explanation, the resin-specific peak is designated as A, and the high-temperature peak that appears on the higher temperature side is designated as B. A straight line (α-β) was drawn connecting point α corresponding to 80°C on the DSC curve and point β on the DSC curve corresponding to the melting end temperature T of the expanded beads. The melting end temperature T refers to the intersection point between the DSC curve on the high-temperature side of the high-temperature peak B and the high-temperature side baseline. Next, a straight line parallel to the vertical axis of the graph was drawn from point γ on the DSC curve that corresponds to the valley between the resin-specific peak A and the high-temperature peak B, and the point where it intersects with the straight line (α-β) was designated as δ. The area of ​​high-temperature peak B was the area surrounded by the curve of high-temperature peak B in the DSC curve, the line segment (δ-β), and the line segment (γ-δ), and was defined as the heat of fusion of the high-temperature peak.

[0091] (Closed bubble rate) The closed cell ratio of the expanded beads was measured using an air comparison type specific gravity meter based on ASTM D2856-70. Specifically, first, the bulk volume of the expanded beads after conditioning, that is, the value of the mark when naturally piled up in a measuring cylinder, was measured. 3After the measurement sample was taken so that the apparent volume of the measurement sample was measured. The apparent volume of the measurement sample is specifically the volume equivalent to the rise in the liquid level when the measurement sample is submerged in a graduated cylinder containing ethanol at a temperature of 23°C. After the measurement sample whose apparent volume was measured was thoroughly dried, the true volume of the measurement sample was measured using an air comparison specific gravity meter 930 manufactured by Toshiba Beckman Co., Ltd. in accordance with procedure C described in ASTM-D2856-70. Using these volume values, the closed cell ratio of the measurement sample was calculated based on the following formula (8). The above operation was performed five times using different measurement samples, and the arithmetic average value of the closed cell ratio obtained by these five measurements was taken as the closed cell ratio of the expanded particles. Closed cell ratio (%)=(Vx-W / ρ)×100 / (Va-W / ρ) (8) However, Vx in the above formula (8) (unit: cm 3 ) is the true volume of the foamed bead (i.e., the sum of the volume of the resin that composes the foamed bead and the total volume of the air bubbles in the closed cell part within the foamed bead), and Va (unit: cm 3 ) is the apparent volume of the foamed beads (i.e., the volume measured from the rise in the liquid level when the foamed beads are submerged in a graduated cylinder containing ethanol), W (unit: g) is the mass of the measurement sample, and ρ (unit: g / cm 3 ) is the density of the polypropylene resin constituting the foamed core layer.

[0092] (average bubble diameter) The average bubble diameter of expanded beads was measured as follows. Twenty expanded beads were randomly selected from a group of expanded beads. The expanded beads were cut through the center and divided into two, and an enlarged photograph of the entire cross section of each was taken using a scanning electron microscope. In each cross-sectional photograph, four lines were drawn at an equal angle (45°) from the outermost surface of the expanded bead through the center to the outermost surface on the opposite side. The number of bubbles intersecting each line was counted, and the total length of the four lines was divided by the total number of bubbles intersecting the lines to determine the bubble diameter of each expanded bead. The value obtained by arithmetically averaging these values ​​was taken as the average bubble diameter of the expanded beads.

[0093] (Aspect ratio (L / D)) The aspect ratio L / D of the expanded beads was determined by measuring the maximum axial length (L) and the maximum cross-sectional diameter (D) of the cross-section of the particle in a direction perpendicular to the longitudinal direction of the maximum length with a vernier caliper for 100 randomly selected expanded beads, calculating the ratio (L / D), and then taking the arithmetic average of these values.

[0094] (Average thickness of coating layer) The average thickness of the coating layer of the expanded beads was obtained by the above method. Specifically, the values ​​calculated by the above formulas (1) to (3) were shown in Table 2 as the average thickness of the coating layer of the expanded beads.

[0095] (Adhesiveness) The adhesion between the foamed core layer and the coating layer of the expanded beads was evaluated by the following method. 1,000 expanded beads obtained in the Examples and Comparative Examples were randomly taken out and visually observed. Specifically, the expanded beads were observed to see whether or not there were any parts of the coating layer peeled off from the foamed core layer. The observation results were evaluated according to the following criteria. Expanded beads without peeling of the coating layer are preferred because they have excellent adhesion to the coating layer. (Evaluation Criteria) A: Less than 5 foam particles have areas where the covering layer has peeled off from the foam core layer. B: 5 or more foam particles have a portion where the covering layer is peeled off from the foam core layer.

[0096] (Lower limit molding pressure) After drying the expanded beads at 23°C for 24 hours, the expanded beads were pressurized to apply internal pressure to the bubbles in the expanded beads so that the pressure of the bubbles became the particle internal pressure shown in Table 2. The expanded beads were filled into a flat mold measuring 250 mm long x 200 mm wide x 50 mm thick, with the cracking amount adjusted to 10% (i.e., 5 mm), and the mold was clamped and steam was supplied from both sides of the mold for 5 seconds to perform an exhaust process of preheating. Thereafter, steam was supplied from one side of the mold until a pressure 0.04 MPa (G) lower than the predetermined molding pressure was reached, and one-sided heating was performed. Next, steam was supplied from the other side of the mold until a pressure 0.02 MPa (G) lower than the molding pressure was reached, and then heating was performed until the predetermined molding pressure was reached (i.e., main heating). After heating was completed, the pressure was released, and the molded body was cooled with water until the surface pressure due to the foaming force of the molded body became 0.04 MPa (G), and then it was released from the mold. The molded body after demolding was aged in an atmosphere of 80°C for 12 hours, and then left to stand in an atmosphere of room temperature until the temperature of the molded body became the same as room temperature (23°C), and a molded body was obtained. The obtained molded body was evaluated for three items, namely, fusion property, surface property, and recovery property, according to the criteria described below, and a molded body that passed all the evaluations was determined to be an acceptable product. In this specification, a molded body that passed both the surface property and recovery property was evaluated as a molded body with good appearance. The molding and evaluation of the above molded products were performed by changing the molding pressure in increments of 0.02 MPa between 0.10 and 0.28 MPa (G), and the lowest molding pressure at which an acceptable product could be obtained was determined as the lower limit molding pressure. The lower the lower limit molding pressure, the better the moldability of the expanded beads, and the less steam is required for molding.

[0097] (Fusing ability) The molded body was bent and broken, the number of foamed particles present on the fracture surface C1 and the number of broken foamed particles C2 were determined, and the ratio of the number of broken foamed particles to the number of foamed particles present on the fracture surface (i.e., material breakage rate) was calculated. The material breakage rate was calculated from the formula C2 / C1×100. The above measurement was carried out five times using different test pieces, and the material breakage rate was calculated for each. A material breakage rate of 80% or more was deemed to be acceptable.

[0098] (superficial) A 100 mm x 100 mm rectangle was drawn in the center of the molded product, and then a diagonal line was drawn from one corner of the rectangle. The number of voids (gaps between expanded beads) larger than a square with sides of 2 mm that were formed so as to overlap with the diagonal line and gaps resulting from through-holes in the expanded beads were counted, and a total of less than 5 was deemed to have passed the test.

[0099] (Recoverability) The thickness of the molded body obtained using a flat mold 250 mm long, 200 mm wide, and 50 mm thick was measured near the four corners (specifically, 10 mm inward from the corners toward the center) and at the center (the part that divides the body into two equal parts in both the vertical and horizontal directions). Next, the ratio (unit: %) of the thickness of the thinnest part to the thickness of the thickest part among the measured parts was calculated, and a ratio of 98% or more was deemed to have passed.

[0100] (Short-time curing formability) A molded body was obtained in the same manner as in the molding at the above-mentioned (lower limit molding pressure), except that the molding pressure was set to the lower limit molding pressure shown in Table 2, and the molded body after demolding was cured for 2 hours in an atmosphere at 80° C. The above-mentioned (recovery property) was evaluated for the obtained molded body, and the better the recovery property after 2 hours of curing, the more stable the dimensions will be even if the curing time is shortened, and the more preferable it is. (Evaluation Criteria) A: The recovery after 2 hours of curing is acceptable (the ratio of the thickness of the thinnest part of the molded body to the thickness of the thickest part is 98% or more) B: The recovery after 2 hours of curing is unacceptable (the ratio of the thickness of the thinnest part to the thickness of the thickest part of the molded body is less than 98%)

[0101] <Expanded bead molding> The following measurements and evaluations were carried out on the expanded bead moldings of the Examples and Comparative Examples. The density of the moldings was measured using the moldings obtained at the lower limit molding pressure in the above-mentioned (lower limit molding pressure). The moldings were left to stand for 24 hours under conditions of 50% relative humidity, 23°C, and 1 atm to condition them before use in the measurements.

[0102] (density) The weight of the expanded bead molding is divided by the volume calculated based on the dimensions to give the molding density (kg / m 3 ) was decided.

[0103] [Raw materials] The resins used in the examples and comparative examples are shown in Table 1. In Tables 1 and 2, the resin names "LL" 1 to 4 and the structure "LLDPE" are linear low-density polyethylene, and "PP" 1 to 5 are polypropylene resins. The structure "Et-Bt-PP" is an ethylene-butene-propylene copolymer, and "Et-PP" is an ethylene-propylene copolymer.

[0104] [Table 1]

[0105] Examples 1 to 3 and Comparative Examples 1 to 5 <Preparation of multi-layered resin particles> A polypropylene-based resin shown in Table 2 was melt-kneaded in an extruder at a maximum set temperature of 240°C to obtain a resin melt for the core layer. At the same time, a linear low-density polyethylene or polypropylene-based resin shown in Table 2 was melt-kneaded in an extruder at a maximum set temperature of 240°C to obtain a resin melt for the coating layer. Next, the molten resin for the core layer and the molten resin for the coating layer were supplied to a co-extrusion die, where they were laminated by co-extrusion so that the molten resin for the coating layer covered the lateral surface of the molten resin for the core layer. The resulting strand was then extruded and cooled with water, and cut into pieces with a pelletizer to a mass of approximately 1.0 mg. The pieces were then dried to obtain cylindrical multilayer resin particles (particle diameter: 2.2 mm, aspect ratio L / D: 2.7). At this time, the amount of the resin melt for the core layer and the amount of the resin melt for the coating layer were adjusted so that the mass ratio of the coating layer to the core layer [mass of the coating layer / mass of the core layer] was the "mass ratio of the coating layer" in Table 2. When producing the multilayered resin particles, zinc borate was supplied to the extruder as a bubble nucleating agent for the resin melt for the core layer. At this time, the bubble nucleating agent was supplied as a master batch, and 1000 ppm by mass of zinc borate was contained as a bubble nucleating agent only in the polypropylene resin of the core layer, and no bubble nucleating agent was contained in the polymer of the coating layer.

[0106] <Preparation of expanded beads> 1 kg of the multilayer resin particles was placed in a 5 L sealed container together with 3 L of water as a dispersion medium, and 0.3 parts by mass of kaolin as a dispersant and 0.2 parts by mass of a surfactant (Neogen, manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.; sodium alkylbenzene sulfonate) (as an active ingredient) were further added to the sealed container relative to 100 parts by mass of the multilayer resin particles, and carbon dioxide as a foaming agent was added to the sealed container so that the pressure inside the container reached the pressure shown in Table 2. The mixture was heated with stirring to the foaming temperature shown in Table 2 and maintained at that temperature for 15 minutes, after which the contents of the container were released under atmospheric pressure to obtain expanded particles (first-stage expanded particles). The coating layer in the expanded particles was in a non-foamed state in all of the Examples and Comparative Examples. Next, the expanded beads were placed in a pressure vessel (specifically, a metal drum), and air was forced into the pressure vessel to increase the pressure inside the vessel, thereby impregnating the air bubbles and increasing the internal pressure inside the bubbles of the expanded beads. Next, steam was supplied to the expanded beads (first-stage expanded beads) taken out of the pressure vessel so that the pressure inside the pressure vessel (i.e., drum pressure) became the pressure shown in Table 2, and the beads were heated under atmospheric pressure. The pressure inside the bubbles (i.e., internal pressure) of the first-stage expanded beads taken out of the pressure vessel was the value shown in Table 2. As a result, the apparent density of the first-stage expanded beads was reduced, and expanded beads (second-stage expanded beads) were obtained. The evaluation results of the obtained expanded beads are shown in Table 2.

[0107] [Table 2]

[0108] It is seen that the expanded beads of the Examples have a significantly low lower limit of molding pressure at which a good molded article having excellent fusibility, surface properties, and recovery can be molded in a mold with a very low steam pressure. It is also seen that the expanded beads of the Examples have excellent recovery, with shrinkage and deformation suppressed even when the curing time in a high-temperature atmosphere is as short as two hours. From the above, it is seen that the expanded polypropylene resin beads of the present invention can significantly reduce the steam pressure during molding in a mold, and can obtain an expanded bead molded article having a desired shape and excellent appearance even when the curing time is shortened.

Claims

1. A polypropylene-based resin expanded particle having a foamed core layer made of a polypropylene-based resin and a coating layer that coats the foamed core layer, The coating layer is made of linear low-density polyethylene, The mass ratio of the covering layer to the foamed core layer is 0.005 or more and 0.05 or less, The polypropylene-based resin expanded particles, wherein the polypropylene-based resin constituting the foamed core layer satisfies the following (i) or (ii): (i) The polypropylene-based resin constituting the foamed core layer is an ethylene-butene-propylene copolymer i, and the total amount Ccmt of the ethylene component and the butene component in the copolymer i (i) is 3.5 mass% or more (ii) the polypropylene-based resin constituting the foamed core layer is one or more copolymers ii selected from an ethylene-propylene copolymer and a butene-propylene copolymer, and the total amount Ccmt of the ethylene component and the butene component in the copolymer ii (ii) is 4.0 mass% or more

2. 2. The expanded polypropylene resin particles according to claim 1, wherein the linear low-density polyethylene constituting the coating layer is a resin polymerized using a Ziegler-Natta type polymerization catalyst.

3. 3. The expanded polypropylene resin particles according to claim 1, wherein the polypropylene resin constituting the foamed core layer has a flexural modulus of 400 MPa or more and less than 800 MPa.

4. The expanded polypropylene resin beads according to claim 1 or 2, wherein the coating layer has an average thickness (Tt) of 0.1 μm or more and 5 μm or less.

5. 3. The polypropylene resin expanded particles according to claim 1, wherein the polypropylene resin constituting the foamed core layer is an ethylene-butene-propylene copolymer i.

6. 3. The expanded polypropylene resin particles according to claim 1, wherein the polypropylene resin constituting the foamed core layer is a resin polymerized using a Ziegler-Natta polymerization catalyst.

7. 3. The polypropylene resin expanded particles according to claim 1, wherein the linear low-density polyethylene constituting the coating layer has a flexural modulus of 120 MPa or more and 600 MPa or less.

8. 3. The expanded polypropylene resin beads according to claim 1, wherein the expanded beads have a bulk ratio of 5 to 45 times.

Citation Information

Patent Citations

  • Polypropylene resin foamed particle and molded product thereof

    JP2000129028A

  • Foamed particle molded object

    JP2003039565A